(untitled) (Eurasian Journal of Engineering and Technology, 2024)
This comprehensive review explores the intricate amalgamation of Polyamide (PA) and Epoxy (EP), two commonly employed polymers with distinct properties. Delving into the chemical reactions between PA and EP, we unearth mechanisms that foster covalent crosslinking, offering avenues for enhanced adhesion. The toughening mechanism of the combined system varies depending on the PA’s integration method, either as a predissolved solution or a discrete phase. Further insights reveal the potential for PA to toughen EP-based composites, invoking principles observed in particle-fortified epoxies. Critical takeaways encompass the optimal balance between PA-induced ductility and system strength and the leverage of blend compositions, configurations, and processing parameters for targeted property enhancement. Whether aiming for moisture resistance, energy absorption, or enhanced adhesion, the PA-EP system provides a versatile platform, showcasing the innovative possibilities within polymer science.